The Brazilian State and the neoliberal attack: some reflections to occupational therapy. - Bezerra, Waldez C (Cadernos de Terapia Ocupacional da UFSCar)
Based on the theoretical framework of the Marxist perspective, this article aims at a theoretical concern about the process of counter-reform in the Brazilian State, based on neoliberal ideas and makes some critical reflections on possible impacts of this process in Occupational Therapy as a profession. In forwarding the reflections the authors who criticize neoliberalism were used to analyze its processes and a critical view of totality, which allowed at the end of the discussion to visualize the regressive nature of ongoing changes implemented by neoliberal adjustment in Brazilian reality in the decade since its inception 1990, as well as to identify some challenges posed by this reality to occupational therapists in contemporary days. For professional employees who are in a state of social policies, it is important to their professional mediation to feel that the inflections in their daily processuality, encountering not only new social demands, but also political barriers to effectuation of a professional project aimed at the protection of social rights.